Perancangan Perpustakaan Dengan Tema “The Shape of Nature” di Grogol - Ulinata; Lintang Bagas H.; Luky Wirawan; Juan Vito Yohanes S. (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Books are windows to the world. In the era of 4.0 which continues to develop and advance, easy access to information and reading books can not only be obtained from the library, now reading can be done via a cellphone from a pocket. This ease of access does not necessarily make people willing to read. According to Unesco, Indonesia's reading interest is in the 2nd lowest rank. UNESCO says Indonesia ranks second from the bottom in terms of world literacy, meaning that reading interest is very low. According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This means that out of 1,000 Indonesians, only 1 person is an avid reader. In a different research titled World's Most Literate Nations Ranked conducted by Central Connecticut State University in March 2016, Indonesia was ranked 60th out of 61 countries in terms of reading interest, just below Thailand (59) and above Botswana (61).